The Effect of Discipline, Work Motivation and Work Ability on Employee Performance PT. Bijak Unit Learning Center Bogor - Yusuf Akbar; Sudarijati Sudarijati; Ismartaya Ismartaya (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This study aims to determine the effect of discipline, work motivation and work ability on the performance of employees of PT BIJAK Bogor Learning Center Unit either simultaneously or partially. Questionnaires were distributed to 101 respondents. The results of the validity and reliability tests indicated that all questions were stated to be valid and reliable. The results of multiple correlation analysis stated that there were very strong relationships between discipline, work motivation and work ability on the performance of employees of PT BIJAK, the result of the coefficient of determination can be explained by 70.8%. The multiple regression analysis F test (simultaneous) states that there is a positive and significant effect simultaneously between discipline, work motivation and work ability on the performance of employees of PT WISE. The results of the t (partial) test state that discipline has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance, and work ability has a positive and significant effect on employee performance at PT. BIJAK Bogor Learning Center Unit.